Crisis of the sugar-energy sector in Brazil and the territorial vulnerability of sugarcane municipalities - Faria-Dos-santos, Henrique; Sampaio, Mateus-De-Almeida-Prado [UNESP]; Mesquita, Fernando; Pereira, Mirlei-Fachini-Vicente (Pontificia Universidad Catolica de Chile, 2022)
In the second decade of the xxi century, the Brazilian sugar-energy sector faced a moment of crisis. Many sugarcane processing plants started a judicial recovery plan or declared bankruptcy and closed their units. These decisions impact the economy of municipalities that are associated with sugarcane production and processing, resulting in local crisis. Considering this scenario, this paper aims to evaluate the different degrees of the territorial vulnerability of municipalities with sugar-energy units. The methodology is based on a proposal of a territorial vulnerability index (ivt) created from the combination of indicators related to the specialization degree, the economic and populational density, and the distinct productive characters of the sugar-energy companies. A map of these results is presented showing the different forms of vulnerability. The most significant cases are municipalities with low demography level, which economies deeply depends on sugarcane production and processing.
Crise do setor sucroenergético no Brasil e a vulnerabilidade territorial dos municípios canavieiros
Keywords: economic crisis; regional and local development; vulnerability